DOMINATED INDIVIDUALSâ€™ TACTICS TO DISRUPT BEING OTHERED IN NEO-COLONIAL NOVELS OF BAUTISTA AND WA THIONGâ€™O - Pableo, Marvin (Sanata Dharma University, 2020)
Dominated subjects or those Othered in many societies are among the most misrepresented class of people. Such misrepresentation has popularised their being imagined in literature and other fields of study as almost always despondent and meek individuals. In this context, this paper interrogates Western archetypal images on Others as passive recipients of domination. Applying De Certeauâ€™s concept of â€œtacticsâ€, this paper investigated how tactics of dominated subjects become immediate yet temporary solution among Others to disturb the everyday practices of Othering. Lualhati Bautistaâ€™s Gapo and Ngugi Wa Thiongâ€™oâ€™s Matigari were scrutinised through discourse analysis and both revealed that â€œeverydayâ€ tactics are used by Othered characters to grapple with, respond to and, later on, overcome societyâ€™s exclusionary practices. Set in the after colonial environs, the novels portray Othered characters as capable of resistance and agency despite their political, economic and/or cultural marginalisation. Such use of tactics as means of resistance are however temporary and, ultimately, cannot solve their being dominated. Nonetheless, the counter-discourse this frame of thought offers as well as how tactics provides space and how space simultaneously allows the production of tactics can provide us a more nuanced understanding of resistance and the lived experiences of Others.